Expression and Purification of Novel Peptide-Based Recombinant Proteins Targeting Breast Cancer Stem Cells - Agusta, Istiqomah; Triwidyaningtyas, Silvia; Bela, Budiman; Mardiana, Mardiana; Wanandi, Septelia Inawati (Writing Center IMERI FMUI, 2025)
Introduction: Peptides with specific affinity toward breast cancer stem cells (BCSCs), including GYSASRSTIPGK and GAIRIRLSEPLS, have gained interest in targeted cancer diagnostics; however, the low abundance of BCSCs often results in limited detection sensitivity. This study addresses this limitation by conjugating BCSC-specific peptides to self-assembling Human Papillomavirus (HPV16) L1 protein, resulting in virus-like particles composed of 72 pentamers that provide substantial signal amplification. In addition, the SpyTag–SpyCatcher system derived from the Streptococcus pyogenes CnaB2 domain provides a robust strategy to enhance peptide–protein stability. Objectives: This study aimed to express and purify three recombinant proteins as key components for assembling a BCSC-specific diagnostic construct: HPV16 L1–SpyTag, SpyCatcher–GYSASRSTIPGK, and SpyCatcher–GAIRIRLSEPLS. Methods: Recombinant genes encoding the target proteins were expressed in Escherichia coli (E. coli) BL21(DE3) following IPTG induction for 1–4 hours. Bacterial cells were harvested and lysed under native or denaturing conditions, and recombinant proteins were purified using Ni-NTA affinity chromatography. Results: SDS–PAGE analysis showed clear bands at the expected molecular weights for HPV16 L1–SpyTag (58.5 kDa), SpyCatcher–GYSASRSTIPGK, and SpyCatcher–GAIRIRLSEPLS ( 15 kDa), with induction-dependent increases in band intensity. The SpyCatcher–peptide fusions were predominantly soluble and purified under native conditions, whereas HPV16 L1–SpyTag was largely insoluble and required denaturing purification. Conclusion: HPV16 L1–SpyTag and SpyCatcher–peptide fusions were successfully expressed and purified in E. coli, establishing a versatile platform with potential to enhance BCSC-targeted detection and treatment strategies in breast cancer.